Acoustic study on the outbreak of Creseise acicula nearby the Daya Bay Nuclear Power Plant Base during the summer of 2020. (April 2021) - Zeng, Lei; Chen, Guobao; Wang, Teng; Zhang, Shufei; Dai, Ming; Yu, Jie; Zhang, Chaowen; Fang, Jianjun; Huang, Honghui
Abstract: From the mid-June to mid-July 2020, there was a massive bloom of Creseise acicula nearby the waters of Daya Bay Nuclear Power Plant Base (DNPP base). In order to find out the spatiotemporal dynamic characteristics of C. acicula and the main factors related to its outbreak and extinction, acoustic surveys and in-situ observations were performed. The results showed that the average abundance of C. acicula at the in-situ observation site fluctuated with the tidal rhythm. Furthermore, a horizontal migration pattern during ebb tide and a vertical subsidence trend of C. acicula was found. The outbreak of C. acicula bloom nearby the waters of DNPP base was the result of the joint action of water temperature, salinity and food availability etc . The extinction of C. acicula was mainly related to the adhesion of Licmophora, predation pressure from phytoplanktivorous fishes (such as Sardinella lemuru and Dussumieria elopsoides ) and human intervention. Highlights: The abundance of C. acicula broke out in china in summer of 2020 was the highest ever. The spatiotemporal dynamic characters of C. acicula were monitored by acoustic method. The outbreak of C. acicula was mainly related to water temperature, salinity, and Chl-a. The extinction of C. acicula was related to natural regulation and human intervention.